Cellular oxidative stress stimulated by microcystin: review (Research, Society and Development, 2021)
Introduction: Cyanobacteria are organisms capable of producing a high number of bioactive molecules, known as cyanotoxins. Among the cyanotoxins, microcystins stand out, compounds with hepatotoxic potential. Studies claim that the most common and most toxic isoform among microcystins is microcystin-LR. One of the most frequently detected properties of microcystins is their ability to generate cellular oxidative stress. Thus, the present study is a bibliographic research about the biochemical mechanism of free radical generation caused by Microcystin LR. Methodology: for the preparation of this review, a survey was carried out in the national and international literature. The inclusion criteria for the construction of this work were original and review articles that addressed the ability of microcystin LR to generate oxidative damage. Results: Once they enter the body, microcystins accumulate in the liver, so that toxicity is associated with specific inhibition of protein phosphatase 1 and 2A (PP1 and PP2A), leading to disruption of cell integrity. Studies prove that MCs produce oxidative stress in vitro and in vivo and that they can act as tumor promoters. Conclusion: there is a possible relationship between cellular oxidative stress caused by microcystin. Thus, cyanobacterial blooms represent a threat to the health of several animals, including man, however, further studies on the topic addressed are needed.